Making Markets: Unpacking Design and Governance of Carbon Market Mechanisms - Prag, Andrew (OECD/IEA Climate Change Expert Group Papers, 2012)
Carbon market mechanisms such as emissions trading systems and crediting mechanisms can have multiple objectives. A key goal is to lower the cost of achieving greenhouse gas (GHG) emissions reductions. Market mechanisms can also catalyse investment in low carbon technologies and practices, provide local environmental and health benefits, contribute to fostering innovation, provide a source of government revenue and facilitate more ambitious mitigation action in future. They can therefore play an important role in the diverse policy toolkit needed to address the global issue of climate change. This paper identifies the key design elements of market mechanisms and examines the governance structures and decision-making processes used to create tradable GHG units in existing systems both inside and outside of the UNFCCC. The analysis explores the potential involvement of international, national and sub-national regulatory bodies in the governance and decision-making processes and the possible role that internationally-agreed standards could play in providing confidence in the quality of GHG units